«Prancing elephant», «K2» and others (local bookselling groups as the regional book business base) - O. N. Alshevskaya (Библиосфера, 2016)
Contemporary bookselling infrastructure in modern Russia is poorly developed. The general negative trends are particularly acute in regions. The article contains the analysis results of bookselling content in Siberian cities. Multiple levels of bookselling infrastructure state are revealed. Large cities (Novosibirsk, Omsk, Krasnoyarsk) refer to a highly evolved level, among which Novosibirsk is the largest center of wholesale and retail book trade in the Eastern Russia. A great number of local bookselling network formations are in Omsk, Krasnoyarsk, Barnaul, and others. Specialized bookselling enterprises are presented at the book market of the Siberian cities: selling foreign literature (Krasnoyarks), children books (Krasnoyarsk), autobooks (Omsk), etc. Large networks effect greatly the regional book market. They are: Irkutsk «ProDalitЪ» (47 stores) and Novosibirsk «Aristotel’» (22 bookshops). Book trade of polar Norilsk is original and formed mainly by local publisher «Apex». In general, the modern book-selling landscape of Siberia is diverse and characterized by an extreme unevenness of the book business enterprises distribution. The local bookselling groups preservation and development is the basis and guarantee of the book culture development in the region.